25-Hydroxyvitamin D supplementation and health-service utilization for upper respiratory tract infection in young children - Omand, Jessica A; To, Teresa; O’Connor, Deborah L; Parkin, Patricia C; Birken, Catherine S; Thorpe, Kevin E; Maguire, Jonathon L (Public health nutrition, 2017)
Upper respiratory tract infections (URTI) are the most common and costly condition of childhood. Low vitamin D levels have been hypothesized as a risk factor for URTI. The primary objective was to determine if serum vitamin D levels were associated with health-service utilization (HSU) for URTI including hospital admission, emergency department visits and outpatient sick visits. The secondary objectives were to determine whether oral vitamin D supplementation in pregnancy or childhood was associated with HSU for URTI. Cohort study. HSU was determined by linking each child's provincial health insurance number to health administrative databases. Multivariable quasi Poisson regression was used to evaluate the association between 25-hydroxyvitamin D, vitamin D supplementation and HSU for URTI. Toronto, Canada. Children participating in the TARGet Kids! network between 2008 and 2013. Healthy children aged 0-5 years (n 4962) were included; 52 % were male and mean 25-hydroxyvitamin D was 84 nmol/l (range 11-355 nmol/l). There were 105 (2 %), 721 (15 %) and 3218 (65 %) children with at least one hospital admission, emergency department visit or outpatient sick visit for URTI, respectively. There were no statistically significant associations between 25-hydroxyvitamin D or vitamin D supplementation and HSU for URTI. A clinically meaningful association between vitamin D (continuously and dichotomized at <50 and <75 nmol/l) and HSU for URTI was not identified. While vitamin D may have other benefits for health, reducing HSU for URTI does not appear to be one of them.